Meteor fluxes and visual magnitudes from EISCAT radar event rates: a comparison with cross-section based magnitude estimates and optical data - A. Pellinen-Wannberg; A. Westman; G. Wannberg; K. Kaila (Annales Geophysicae, 1998)
Incoherent scatter radars (ISR) are versatile instruments for continuous monitoring of ionisation processes in the Earth's atmosphere. EISCAT, The European Incoherent Scatter facility has proven effective also in meteor studies. The time resolution of the radar can be reduced to a few milliseconds, sufficient to resolve the passage of individual meteors through the narrow ISR beam. Methods for group and phase velocity determination of the meteoroids and the discrepancy between the results related to the target behaviour are presented. The radar cross sections of echoes associated with moving meteoroids ("meteor head echoes") are very small and increase with decreasing wavelength. The parent meteoroids are found to have visual magnitudes far below the detection limit of most optical observations. The equivalent visual magnitude limit of the smallest objects observed by EISCAT in the current experiments has been estimated by two different methods, both from the cross-section measurements and from the measured event rates. Both methods give a limit value of +10 for the smallest objects while the upper limit is +4. The lower limit of the visual magnitude for the collocated optical measurement system is +4. Thus the two detection systems observe two different meteor size ranges, with the radar almost reaching micrometeorite population. Meteor fluxes estimated from the event rates and the radar system parameters agree well with previous extrapolated values for this size range. Key words. Ionosphere (ionization mechanisms). Radio science (ionospheric physics). Space plasma physics (ionization processes)